PERBANDINGAN PENGAKUAN PENDAPATAN ANTARA STANDAR AKUNTANSI KEUANGAN (SAK) INDONESIA DENGAN USULAN KONVERGENSI IFRS DAN U.S. GAAP - Muhammad Syam Kusufi (LPPM Universitas Trunojoyo Madura, 2013)
This study tries to compare the revenue recognition of Financial Accounting Standards (GAAP) with IFRS and U.S. GAAP Convergence. As it is known that during the recognition of revenue in Indonesia are often more frequent use of Financial Accounting Standards (GAAP). This study outlines where the advantages and drawback between the two revenue recognition.